THE LABORATORY PERSPECTIVE OF LEUKOCYTE DIFFERENTIAL, LYMPHOCYTE COUNT AND CELL POPULATION DATA IN EVALUATION OF SARSCOV2: A COMPREHENSIVE SYSTEMATIC REVIEW - Paranoan, Anissa; Paranoan, Anelsa (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The pathology of COVID-19 involves a dysregulation of the adaptive immune system, with hematological abnormalities being frequently reported in affected patients since the onset of the pandemic. Specifically, leukocyte differentials in SARS-CoV-2 infected individuals often exhibit neutrophilia, lymphopenia, and morphology alterations. This study aims to serve a comprehensive systematic review to examine the role of leukocyte differential, lymphocyte count, and CPD parameters to evaluate SARS-COV2 in literatures of the last 10 years. Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. It excluded editorials, review papers from the same journal, and submissions lacking a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 937 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: The comprehensive assessment of leukocyte count, lymphocyte count, and cell population data provides invaluable insights into the immune dysregulation and disease severity in COVID-19 infection. Understanding the intricate interplay between these hematological parameters can guide clinicians in early detection, risk stratification, and tailored therapeutic interventions for patients battling COVID-19.